MOUNTAIN-FRONT SINUOSITY AND ASYMMETRICAL FACTOR OF LELES-GARUT INTRA-ARC BASIN, WEST JAVA - Haryanto, Iyan; Setiadi, Djadjang Jedi; Alam, Syaiful; Ilmi, Nisa Nurul; Sunardi, Edy (Journal of Geological Sciences and Applied Geology, 2018)
The Leles-Garut Basin, with an elevation ranges between 650 and 725 above mean sea level, is a Quaternary topographic basin area situated in the east-trending volcanic arc of West Java. In contrast to the adjacent Bandung Basin, the nature of the basin bounding area of the Leles-Garut Basin is not clearly defined. The presence of volcanic chain and structural lineament exhibits the difference in morphological features. A quantification of morphological indices was chosen to redefine an active tectonic involvement in surrounding basin border. Mountain-front sinuosity indices range from 1.1 to 3.9 and basin asymmetrical factor suggests a wide range of the effects of active tectonic even a little tilting. The study unveil that the basin bounding is not only volcano-bounded but also fault-bounded.